Combined convective heat and airborne pollutant removals in a slot vented enclosure under different flow schemes: Parametric investigations and non unique flow solutions. (5th February 2016) - Ren, Xiu-Hong; Hu, Jiang-Tao; Liu, Di; Zhao, Fu-Yun; Li, Xiao-Hong; Wang, Han-Qing
Highlights: Combined convective heat and airborne transports under different flow schemes. Natural and forced convection dominated regimes were identified with transition. Dual solution branches were sustained for the transitional mixing flow scheme. Rest solutions evolving from motionless flows coincided with other solution branch. Heat and species lines were presented to delineate heat and mass transport structures. Abstract: This paper reports a numerical study of mixed convection on a heated and polluted strip within a slot ventilated enclosure in which the displacement and mixing flow schemes are considered. Contours of streamfunction, heatfunction, and massfunction are presented to clearly scrutinize the mechanism of heat and airborne pollutant transports. For the displacement flow scheme, thermal Nusselt and pollutant Sherwood numbers under different Reynolds numbers remain almost constant as the value of Gr/Re 2 decreases down to the regime of forced convection dominated. However, as Ar increases up to the regime of natural convection dominated, both Nu and Sh increase sharply with Ar ( Gr/Re 2 ). Similar trends could be observed for the situation of mixing ventilated flow scheme. In the mixing scheme, non unique steady flow solutions could be observed for the range of transitional flow regime. Upward solutions, downward solutions and rest solutions have been exemplified with varying Gr / Re 2 . Dual solution branches could be sustained at the range of 39.0 ≤ Gr/Re 2 ≤ 6.0 × 10 3, while the rest solutions obtained from rest states were completely coinciding with former continuous solutions. The present work could be significant for the natural optimization and passive control of heat and pollutant removals from the electronic boxes or building enclosures.